Locked on - Clancy, Tom, 1947-2013.; Greaney, Mark. (New York : Berkley Books, 2012)
Coming out of retirement to run for president, Jack Ryan finds himself in the middle of a high-stakes attack from his opponent as his close comrade, John Clark, is the subject of treacherous charges, at the same time Jack Ryan, Jr. and other members of Campus struggle to stop terrorists.
Keywords: Ryan, Jack, -- Sr. (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Terrorists -- Fiction; Presidential candidates -- United States -- Fiction; Intelligence officers -- Fiction; Political fiction; Action and adventure fiction; Thrillers (Fiction); Fiction; Political fiction